Maternal Nutrition: Eating for two for the welfare of pregnancy and progeny? - Pacora, Percy (2015)
Although there is no doubt that it is necessary to improve the pregravid nutritional status or indicate caloric supplements since early in pregnancy in undernourished woman, it is also important to avoid excessive nutrients during pregnancy in normal and overweight women. Should there exist familiar predisposition to develop arterial hypertension, dyslipidemia or diabetes mellitus, these women will develop such diseases during pregnancy with catastrophi, consequences to the mother and her infant. The excesive weight gain after each delivery will cause obesity with the subsequent risk of developing the above diseases early in life. Mother’s nutritional habits is transmitted to progeny in pregnancy which added to the environmen will determine the development of chronic diseases by generations. Therefore, it is imperative to keep an appropiate maternal nutrition as a key for health in pregnancy and progeny.